Detection of aberrant glycosylations in head and neck squamous cell carcinomas - Rekola, Juha (My University, 2021)
Head and neck squamous cell carcinomas (HNSCC) are very aggressive types of cancers that cause around 300 000 deaths annually. Being the sixth most frequent type of malignancy globally, consumption of both tobacco and alcohol as well as infections caused by Human papillomavirus (HPV) are the most universal causatives for HNSCC. The aim of this study was to develop a simple, noninvasive method for HNSCC detection from patient’s blood sample using tumor-specific antibodies as captures and lectin-coated nanoparticles (NPs) as tracers. Specifically, a suitable biomarker that enables fast and reliable detection in case of regenerating cancers was identified. Additional sialyl-Tn (sTn) binders were produced as binders using bacterial alkaline phosphatase (BALP) fusion protein and pLK06H-scFv as vector. In-house developed, time-resolved fluorescence (TRF) assay using glycan-specific antibodies coated on the surface of Eu3+-NPs as tracers was used for the discovery of novel serum marker. The results showcase that one integrin-lectin combination (bITGA6-UEA-NPs) was superior for detecting HNSCC from serum samples when measuring Europium from surface. Additionally, one of the produced sTn clones combined with UEA (G4-UEA-NPs) showed clinical significance. However, this work was performed with relatively minimal sample amounts and needs to be repeated in larger sample volumes before they can be reliably implemented in clinical settings.
Keywords: head and neck squamous cell carcinomas, integrin, lectin, immunoassay